2008
DOI: 10.2465/jmps.071015
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of olivine-group minerals

Abstract: , respectively, and their ω (= κ 1 -κ 2 ) value is fairly constant around 32 cm. On the other hand, fayalite, tephroite, and other olivine -group minerals in which transition elements exist in the M2 site have a fairly constant κ 1 (836 -839 cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
92
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 19 publications
18
92
1
3
Order By: Relevance
“…1 and eqn. 2 are consistent with previously published results (e.g., Wang et al, 2004;Mouri and Enami, 2008). Several studies showed that the relations between the peak positions and Mg# are not linear in the case of both peak 1 and peak 2 (Kuebler et al, 2007;Mouri and Enami, 2008) or that the regression can be divided into two Mg# regions (Gaisler and Kolesov, 2007).…”
Section: Mg# Dependencesupporting
confidence: 82%
See 1 more Smart Citation
“…1 and eqn. 2 are consistent with previously published results (e.g., Wang et al, 2004;Mouri and Enami, 2008). Several studies showed that the relations between the peak positions and Mg# are not linear in the case of both peak 1 and peak 2 (Kuebler et al, 2007;Mouri and Enami, 2008) or that the regression can be divided into two Mg# regions (Gaisler and Kolesov, 2007).…”
Section: Mg# Dependencesupporting
confidence: 82%
“…Understanding the relationship among the Raman peak positions, Mg#, and residual pressure enables a simultaneous determination of both Mg# and residual pressure. The relationship between the peak positions and Mg# of olivine has been examined under ambient pressure (e.g., Wang et al, 2004;Kuebler et al, 2006;Gaisler and Kolesov, 2007;Mouri and Enami, 2008). In contrast, the pressure dependence of the Raman spectra of olivine has been examined only for forsterite (e.g., Chopelas et al, 1990;Wang et al, 1993;Durben et al, 1993) and for olivine with Mg# of 90 (e.g., Besson et al, 1982;Rouquette et al, 2008); no systematical study on various Mg# has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…When the ion concentration exceeds a few wt% (locally), olivine silicate (Co 2 SiO 4 ) or cobalt aluminate spinel (CoAl 2 O 4 ) precipitates out [45,46], in both lead-based (soft paste) or silica-rich (hard paste) glazes respectively. The olivine Raman signature has doublet at about 825 cm -1 [68].…”
Section: Raman Signaturesmentioning
confidence: 99%
“…1: actually the black area appears dark blue under high-power illumination). The Raman spectrum of olivine (Co 2 SiO 4 ) also exhibits its stretching doublet in the same wavenumber range [47], but the peak bandwidth is much narrower. The intensity of Si-O stretching tends to be much lower than that of As-O because of the smaller polarizability and the lower number of electrons involved in the bond.…”
Section: Pigmentsmentioning
confidence: 99%